The treatment of section 24J instruments denominated in a foreign currency with regard to the categorisation as fixed or variable rate instruments and the interaction between section 24J, section 25D (foreign currency translation rules) and section 24I (gains and losses on foreign exchange transactions) - Fourie, Susanna Janine. (Department of Finance and Tax, 2016)
Section 24J is regarded to be one of the most complex provisions in the Income Tax Act No. 58 of 1962. This study specifically focuses on the income tax treatment of section 24Jinstruments denominated in a foreign currency, specifically with regards to whether such instruments are fixed or variable rate instruments for purposes of section 24J and the interaction between section 24J, section 25D (foreign currency translation rules) and section 24I (gains and losses on foreign exchange transactions).The basic concepts surrounding the incurral and accrual of interest for income tax purposes, as well as of some of the general issues faced when section 24J is practically applied are discussed. Importantly it is found that although the definition of 'instrument' includes all debt instruments, regardless of whether such instruments are interest-bearing, the application of section 24J would have no impact on the issuer or holder of an instrument that is a non-interest bearing debt instrument. Also, the section 24J definition of 'interest' is wider than the common law meaning of the same term. However, as 'interest'is defined with reference to itself, the common law meaning is still very relevant. It is confirmed that section 24J poses various interpretational uncertainties which are especially highlighted when some of the key provisions of section 24J are applied in determining the interest accrual amounts based on the yield to maturity method. Applying the rules of statutory interpretation and with the aid of hypothetical examples, itis argued that foreign exchange rates would fall within the definition of a variable rate for purposes of section 24J. However, an instrument denominated in a foreign currency would be regarded as a fixed rate instrument to the extent that the amounts payable are fixed amounts specified in the applicable foreign currency or the calculation of the amount payable in the applicable foreign currency does not involve the application of a 'variable rate' (as defined).Further is it argued that section 24J merely provides for a single accrual or incurral event during each year of assessment in relation to each instrument. Therefore, where accrual amounts be denominated in a foreign currency it should be translated at the spot rate on the last day of the year of assessment (or on the date of redemption/transfer in the instance where the instrument was transferred/redeemed during the year of assessment) for purposes of determining the sum of the accrual amounts to be included in taxable income. It is also argued that the timing of the accrual and incurral of interest amounts in terms of section 24J is applied in establishing the 'transaction date' of the interest amount owing for purposes of determining 'exchange differences' at the end of any year of assessment in terms of section 24I.